(untitled) (ItalianoLinguadue, 2017)
Tourism, an important industry with a significant social and cultural dimensions, provides interesting stimuli for the study of communication, particularly in the search for adequate tools for persuading potential clients. Since the internet is an essential tool for self-promotion nowadays, specialists examine how tourist destinations are presented in different types of digital texts such as official tourism websites, which combine the informative function of guidebooks with the promotional function of brochures and leaflets. The purpose of this study is to analyse the rhetorical strategies used on the official homepages of nine Italian regions to catch the eye of potential clients and create an identity for a particular region as a tourist destination. Il turismo, industria importante che ha una significativa dimensione sociale e culturale, costituisce un’area che fornisce stimoli interessanti per lo studio della comunicazione, in particolare nella ricerca di strumenti adeguati a persuadere potenziali clienti. Dal momento che oggi Internet è uno strumento essenziale per l’auto-promozione, molti specialisti si sono dedicati allo studio di come le destinazioni turistiche sono presentate in diversi tipi di testi digitali quali, ad esempio, i siti turistici ufficiali, che combinano la funzione informativa delle guide con quella promozionale di opuscoli e volantini. Scopo di questo studio è analizzare le strategie retoriche utilizzate nelle homepage ufficiali di nove regioni italiane per catturare l’attenzione dei potenziali clienti e per caratterizzare la regione come destinazione turistica.